A novel white spot syndrome virus-induced gene (MjVIG1) from Marsupenaeus japonicus hemocytes. Issue 77 (June 2018) - Zhang, Kehong; Koiwai, Keiichiro; Kondo, Hidehiro; Hirono, Ikuo
Abstract: cDNA of a newly recognized white spot syndrome virus (WSSV)-induced gene (MjVIG1) was characterized from Marsupenaeus japonicus hemocytes; this gene encodes a protein that lack similarity to any known characterized protein. To identify this novel gene, we mainly conducted transcript level analysis, immunostaining and flow cytometry after WSSV infection. MjV1G1 transcript levels were also measured after Yellow head virus (YHV) and Vibrio parahaemolyticus infection tests. In non-infected and WSSV-infected shrimp, MjVIG1 was observed in granule-containing hemocytes. In addition, the MjVIG1 transcript level and ratio of MjVIG1-positive hemocytes both significantly increased, and number of MjVIG1-positive hemocytes slightly increased after WSSV infection. In contrast, MjVIG1 transcript level did not change after YHV and V. parahaemolyticus infection. These results indicated that MjVIG1 might be a WSSV-specific induced gene in M. japonicus hemocytes. Highlights: Full-length MjVIG1 cDNA was identified in Marsupenaeus japonicus hemocytes. MjVIG1 transcripts significantly increased after WSSV infection but not after V. parahaemolyticus and YHV infections. The ratio of MjVIG1+ hemocytes significantly increased and MjVIG1+ hemocytes number slightly increased after WSSV infection. MjVIG1 might be a WSSV-specific induced gene in M. japonicus hemocytes.